Анализа корелационог ризика нивоа сировине RAGE и HLI код пацијената са имунолошким болестима: Ниво серума RAGE и HLI код имунолошких болести - Li, Xin; Zha, Kexin; Xian, Gongxue; Shen, Xueping; Yan, Sheng; Han, Qiuping (Journal of Medical Biochemistry, 2026)
[Objective]: To explore the roles of Human Leukocyte Interferon (HLI) and Receptor for Advanced Glycation Endproducts (RAGE) in the occurrence and development of systemic lupus erythematosus (SLE), as well as their associations with the disease activity and clinical symptoms of SLE, and to evaluate the clinical application value of their detection.[Methods]: The levels of serum RAGE and HLI in SLE patients were detected via ELISA. The immunomagnetic bead method was used to measure the amounts of interleukin (IL)-1β, IL-2, IL-4, IL-5, and IL-6. Serum HLI and RAGE levels in the active and inactive groups were assessed to gauge the effectiveness of the trial.[Results]: The SLE group had higher levels of HLI and RAGE than the RA group (P
Keywords: Системски лупус еритематозус; Анализа корелације; Процена прогнозе; Људски леукоцитни интерферон; Рецептор за крајње продукте гликације